2005
DOI: 10.2320/matertrans.46.167
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Oxidation Resistance of Cu-Al Dilute Alloys by Pre-annealing in H<SUB>2</SUB> and Ar Atmospheres

Abstract: The formation of protective Al 2 O 3 thin layers on Cu-Al dilute alloys and their effect on the oxidation resistance has been investigated at high temperatures. Since selective and preferential oxidation of Al in Cu-Al alloys would take place under the very low oxygen pressures, Cu-Al (Al: 0:22 mass%) alloys were annealed at various temperatures in H 2 and/or Ar atmosphere. Continuous stable Al 2 O 3 thin layers were formed on the specimens annealed in Ar after H 2 annealing. Owing to the protective thin Al 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…There have been many efforts to find the utility of alloying element Al, 6,7 where a continuous Al 2 O 3 layer is formed on the surface of CuAl alloys 8 by a pretreatment or annealing at higher temperature in inert atmosphere where Al reacts with O remnant. [9][10][11] It is found that at T Ͻ 873 K, the necessary alloying amount of Al is smaller than 1 wt %. 10 Because alloying of Mg leads to a lower increase of electric resistivity of Cu than Al due to the strong surface enrichment ability of Mg in Cu, the recent selection principle for alloying element discussed above seems to prefer alloying Mg in Cu.…”
mentioning
confidence: 99%
“…There have been many efforts to find the utility of alloying element Al, 6,7 where a continuous Al 2 O 3 layer is formed on the surface of CuAl alloys 8 by a pretreatment or annealing at higher temperature in inert atmosphere where Al reacts with O remnant. [9][10][11] It is found that at T Ͻ 873 K, the necessary alloying amount of Al is smaller than 1 wt %. 10 Because alloying of Mg leads to a lower increase of electric resistivity of Cu than Al due to the strong surface enrichment ability of Mg in Cu, the recent selection principle for alloying element discussed above seems to prefer alloying Mg in Cu.…”
mentioning
confidence: 99%